Data Flow Based Integration Testing - Vilela, Plínio R. S.; Maldonado, José C.; Jino, Mario (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1999: Anais do XIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1999.23934, 1999)
An approach to extend Structural Unit Testing Criteria to the Integration Testing is presented. The approach is based on the concept of Potential Uses, which basically states that a data flow association exists between a definition of a variable and every point reachable from that definition through a definition-clear subpath, even without an explicit usage of the variable - it is called a potential data flow association. A practical procedure to implement the approach, based on testing information generated during unit testing, is also presented.